PALAEOMAGNETISM OF PROTEROZOIC ROCKS FROM THE UKRAINIAN SHIELD: NEW TECTONIC RECONSTRUCTIONS OF THE UKRAINIAN AND FENNOSCANDIAN SHIELDS - Elming S.-Å.; Mikhailova N.P.; Kravchenko S. (My University, 2001)
A palaeomagnetic study has been performed on Palaeo-Mesoproterozoic rocks from three crustal blocks of the Ukrainian Shield, southern Sarmatia. Primary remanent magnetizations have been isolated in 2.0Ga monzonite, 2.0–1.8Ga sandstone, 1.77–1.72Ga anorthosite and from mafic dykes of probably Palaeo-Mesoproterozoic ages. On basis of these results a sequence of 2.0–1.72Ga apparent polar wander has for the first time been defined for the Ukrainian Shield. Palaeomagnetic and geological data indicate that there has probably not been any large scale tectonic movements within Sarmatia since the Mesoproterozoic. This suggests that tectonic reconstructions for the Ukrainian Shield may also include Sarmatia. The calculated pole positions for the Ukrainian Shield are significantly different from poles of similar age from the Fennoscandian Shield. The tectonic reconstructions demonstrate that the relative position and orientation of the Ukrainian Shield as a part of Sarmatia in the time interval 2.0–1.78Ga was different from its present position relative to Fennoscandia. One pole from the Ukrainian Shield falls on the ca. 1.6 or 1.3Ga part of the Fennoscandian APWP. This pole may represent a time when Fennoscandia was already accreted to Ukrainia. Contemporaneous rifting of the two cratons at ca. 1.35Ga indicates that they were already joined to each other at that time, which means that the final accretion should have taken place sometimes after ca. 1.8Ga ago.
Keywords: Proterozoic; paleomagnetic; Ukrainian Shield; tectonic reconstructions; Precambrian::Proterozoic; Докембрий::Протерозой